Biomaterials and Advanced Technologies for Hemostatic Management of Bleeding. Issue 4 (22nd November 2017) - Hickman, DaShawn A.; Pawlowski, Christa L.; Sekhon, Ujjal D. S.; Marks, Joyann; Gupta, Anirban Sen
Abstract: Bleeding complications arising from trauma, surgery, and as congenital, disease‐associated, or drug‐induced blood disorders can cause significant morbidities and mortalities in civilian and military populations. Therefore, stoppage of bleeding (hemostasis) is of paramount clinical significance in prophylactic, surgical, and emergency scenarios. For externally accessible injuries, a variety of natural and synthetic biomaterials have undergone robust research, leading to hemostatic technologies including glues, bandages, tamponades, tourniquets, dressings, and procoagulant powders. In contrast, treatment of internal noncompressible hemorrhage still heavily depends on transfusion of whole blood or blood's hemostatic components (platelets, fibrinogen, and coagulation factors). Transfusion of platelets poses significant challenges of limited availability, high cost, contamination risks, short shelf‐life, low portability, performance variability, and immunological side effects, while use of fibrinogen or coagulation factors provides only partial mechanisms for hemostasis. With such considerations, significant interdisciplinary research endeavors have been focused on developing materials and technologies that can be manufactured conveniently, sterilized to minimize contamination and enhance shelf‐life, and administered intravenously to mimic, leverage, and amplify physiological hemostatic mechanisms. Here, a comprehensive review regarding the various topical, intracavitary, and intravenous hemostatic technologies in terms of materials, mechanisms, and state‐of‐art is provided, and challenges and opportunities to help advancement of the field are discussed. Abstract : Hemostatic biomaterials and technologies are directed at reducing bleeding complications in trauma, surgery, hematology/oncology, and drug‐induced or congenital blood disorders, to prevent organ damage and improve survival. A comprehensive review and discussion is presented on hemostatic biomaterials and technologies that are currently clinically established, as well as new systems in preclinical and translational development.